Compact and high-resolution plasmonic wavelength demultiplexers based on Fano interference - Chen, Jianjun; Li, Zhi; Jia Li; Qihuang Gong (OPTICS EXPRESS, 2011)
Using strong couplings of different Fabry-Perot (FP) resonators in metal-insulator-metal waveguides, a compact plasmonic wavelength demultiplexer is numerically demonstrated with high wavelength resolution. In the demultiplexer, it is found that new right-angle resonators emerge with bandwidth narrower than that of the isolated FP resonators. These narrowband right-angle resonators interfere with the broadband FP resonators, resulting in Fano-line shapes in the transmission spectra. Consequently, these sharp and asymmetric Fano-line shapes considerably increase the resolution of wavelength demultiplexing, which is significantly narrower than the full width of the isolated FP resonator. (C) 2011 Optical Society of America